The Urgency of Deriving Islamic Law to Ensure Legal Certainty in Indonesia’s Sharia Financial System - Jefik Zulfikar Hafizd; Ahmad Khoirudin; Zelanti Deviana Putri; Nur Arifah; Leliya Leliya (JURNAL AKTA, 2026)
Ensuring legal certainty in Indonesia’s Sharia financial system requires more than formal regulations; it depends on the methodologically accountable derivation of Islamic law (ijtihād) to translate Sharia principles into clear, consistent, and enforceable standards for products, supervision, and dispute resolution. Rapid innovation in financial instruments, increasing regulatory complexity, and the value-based nature of Sharia norms intensify the need for institutional ijtihād that preserves the integrity of the Sharīʿah while remaining operational within a codified national legal order. Normative legal analysis, supported by a focused literature review and an examination of relevant statutory, regulatory, and fatwa materials, is complemented by limited field evidence drawn from purposive interviews with key stakeholders—namely a regional MUI chair, legal scholars, Sharia economics experts, and academics—to validate the practicality and institutional relevance of the arguments advanced. Five integrated strategies are advanced for regulatory strengthening: deepening maqāṣid al-sharīʿah as a normative framework, integrating contemporary ijtihād into regulatory structures, harmonizing institutional roles among DSN–MUI, Otoritas Jasa Keuangan (OJK), and Sharia financial institutions, strengthening education and applied research in Islamic economic law, and pursuing limited codification and standardization of Sharia products. Legal certainty is thereby positioned as an outcome of coherent governance and disciplined Islamic legal reasoning, supporting a Sharia financial system that is substantively just, predictable, and sustainable.